Analisis Kesulitan Mahasiswa Program Studi Pendidikan Fisika Universitas Jember dalam Memahami Konsep Thermodinamika - Handayani, Angel Ika Siswi; Indriyani, Amalia Rosyida; Rosida, Anisa Suci Galuh; Astutik, Sri; Meilina, Ike Lusi (U-Teach: Journal Education of Young Physics Teacher, 2025)
Students often have difficulty understanding complex and abstract thermodynamic concepts, due to differences in learning styles, low digital literacy, and lack of effective media and learning methods. This study aims to identify the causes of these difficulties, determine the most difficult concepts to understand, and formulate appropriate learning strategies to improve student understanding. The research method used is a descriptive quantitative method that is able to provide an objective picture of the students' level of understanding, the various difficulties they experience, and the aspects that affect their learning process. From this research, the results and conclusions were obtained that students tend to have difficulty in understanding abstract concepts of thermodynamics due to ineffective teaching methods and weak basic understanding so that innovative learning strategies that integrate theory and practice are needed to improve understanding